Pengaruh Pemberian Berbagai Sumber Biochar dan Berbagai Pupuk Kandang terhadap Pertumbuhan dan Produksi jagung hitam (Zea mays L.) - Rikwan Kardo Berutu; Rizal Aziz; Sumihar Hutapea (Universitas Medan Area, 2019)
Black corn has its advantage compare to regular corn due to the nutrition component. This could lead the increase of demant to this corn variety. The Effect of providing various biochar sources and various manure on the growthand production of Zea mays black maiz L. The study used factorial randomized block design with two factors, namely the provision of various biochar sources which was combined into several organic fertilizer. Parameters observed were plant height, stem diameter, number of leaves, wet production weight/sample using klobot, wet production weight/plot using klobot,wet production weight/sample without klobot, wet production weight/plot without klobot, dru production weigh of pipil/sample, dry weight of production of onehundred grain pipil. The results of the study showed that the effect of giving various biochar of rice husk corn cobs of candlenut shells did not signficantly affect all observation parameters and various manure, namely cows, chickens and goats also did not significantly affect all observed parameters.